Perbedaan antara Siswa yang Memiliki Tingkat Self-Efficacy Matematis Tinggi dan Rendah Terhadap Minat Belajar Matematika Siswa SMA - Siti Maesaroh; Habibi Ratu Perwira Negara; Kiki Riska Ayu Kurniawati; Syaharuddin Syaharuddin; Habib Ratu Perwira Negara (Universitas Muhammadiyah Semarang, 2024)
This study aims to examine the difference between students with high and low levels of mathematical self-efficacy regarding their interest in learning mathematics at the high school level (SMA). The research design employed is quantitative. Data analysis utilized an independent samples t-test conducted via IBM SPSS Statistics 25. The study involved distributing questionnaires to 51 high school students from grades X, XI, and XII. Data processing included preliminary tests such as normality and homogeneity tests, followed by the Independent Samples t-test with a significance level of 5%. The hypothesis testing results using the Independent Samples t-test indicated a significance value (2-tailed) for equal variances assumed of 0.787 > 0.05, suggesting a difference between students with high and low levels of mathematical self-efficacy concerning their interest in learning mathematics at the high school level.